"Are We Not Foreigners Here?" Indigenous Nationalism in the Twentieth-Century U.S.-Mexico Borderlands - Schulze, Jeffrey (The University of North Carolina Press, 2018)
This book examines efforts by Indigenous Yaqui, Kickapoo, and Tohono O'odham people to maintain sovereignty and identity by utilizing the unique nature and sociopolitical dynamics of the U.S.-Mexico borderlands.